11 Factors affecting the transformation of muscle to meat. (7th December 2018) - England, E
Abstract: When an animal is harvested for meat, a series of biochemical reactions within the skeletal muscle attempts to maintain energy (ATP) homeostasis. To maintain ATP, stored muscle glycogen is catabolized through glycogenolysis to generate ATP through glycolysis. However, as ATP is hydrolyzed, hydrogen ions (H+) are produced that acidify muscle from pH 7.2 in living muscle to pH near 5.5 under normal conditions. The rate of pH decline and the ultimate pH at which this process terminates influences the development of meat quality characteristics. For instance, early termination of pH decline near the pH of living muscle (pH 7.2-6.0) creates meat that is dark in color and conducive for microbial growth. Alternatively, accelerated pH decline or continued acidification of muscle to a low ultimate pH (pH 5.4-5.2) produces meat that is pale in color and exudative. These deviations in postmortem pH decline can arise from a number of external antemortem factors like animal diet, transport, handling, and carcass chilling rates. Because these factors can be confounded, an in vitro buffer system was developed to simulate anaerobic postmortem metabolism to describe the contributions glycogenolysis and glycolysis play in determining ultimate pH and fresh meat quality characteristics. This system utilizes pre-rigor skeletal muscle as the enzyme source and contains the biochemical metabolites necessary for glycogenolysis and glycolysis under different environmental conditions. The buffer system has been able to assess the contribution of individual biochemical reactions and external factors like carcass chilling rate to influence the rate and extent of postmortem pH decline and pork quality development. This system has also been used for similar investigations into ruminant and poultry skeletal muscle. Ultimately, utilizing the in vitro buffer system may improve meat quality by elucidating the biochemical mechanisms regulating the development of meat quality attributes during the transformation of muscle to meat.